(untitled) (The Pakistan Development Review, 2001)
The visible fast increase in the growth rate of world population occurred during the second half of the twentieth century due to the faster declines in mortality following the medical and public health advances made around the time of World War II. The global population growth rate after peaking of at around 1.7 to 1.9 percent per annum in the 1970s and 1980s has since started declining and is currently around 1.4 percent per annum. The world population more than doubled, recording 142 percent increase, from 2.51 billion in 1950 to around 6.07 billion in 2000 [Hakim (2000)]. Most of the increase has been in less developed countries, from 1.68 billion in 1950 to 4.88 billion in 2000, recording 190 percent. Compared to this, the more developed countries witnessed only a marginal increase of 43 percent from 0.83 billion in 1950 to 1.19 billion population in 2000.